A composite catalytic material and its preparation method and application
By using mesoporous silicon-aluminum material as a support in the catalytic material and introducing lanthanum oxide and cadmium oxide as active ingredients, the problem of limited effects of existing catalytic materials in the dehydration and desulfurization process is solved, and efficient moisture and sulfide removal effect is achieved.
Patent Information
- Application Number
- CN202510029481.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing catalytic materials have limited effects in the dehydration and desulfurization process and cannot effectively remove moisture and sulfide from the gas.
A composite catalytic material is used, which consists of mesoporous silicon-aluminum material as the support, and lanthanum oxide and cadmium oxide as the active ingredients. Through a specific preparation method, the active ingredients and the support are coordinated to form a catalytic material with superior dehydration and desulfurization effects.
The composite catalytic material exhibits superior effects in the dehydration and desulfurization process, can effectively remove moisture and sulfides in the gas, and significantly improve the activity and stability of the catalytic material.
Smart Images

Figure BDA0005233739920000091 
Figure BDA0005233739920000101 
Figure BDA0005233739920000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a composite catalytic material and a preparation method and application thereof. Background Art
[0002] The petrochemical industry is related to the prosperity and development of the modern economy and society. Among them, fossil energy such as natural gas, oil, and coal have a great impact on the development and progress of the modern petrochemical industry. The exhaust gas of some fuel gases (such as natural gas) or fossil fuels (such as natural gas, oil, and coal) during combustion contains a large amount of sulfur, which not only corrodes engines and production equipment, but also increases SO X The content of water in the gas may cause acid rain, aggravate climate warming, and endanger human health. The high water content in the gas may form hydrates, which may affect the use of the gas. The water in the exhaust gas from the combustion of fuel gas or fossil fuels may contact with the acidic gas, which may easily form a highly corrosive acidic solution, further causing blockage or physical damage to various valves such as throttle valves, pipelines, and instruments. Therefore, dehydration and desulfurization catalytic materials have attracted everyone's attention. However, the dehydration and desulfurization effects of existing catalytic materials are limited. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing catalytic materials have limited dehydration and desulfurization effects, thereby providing a composite catalytic material and a preparation method and application thereof.
[0004] The present invention provides a composite catalytic material, which comprises a carrier and an active component;
[0005] The carrier is a mesoporous silicon-aluminum material;
[0006] The active ingredients are lanthanum oxide and cadmium oxide.
[0007] Preferably, the pore volume of the composite catalytic material is 0.57-0.84 cm 3 / g, average pore size of 3.2-5.2nm, specific surface area of 420-520m 2 / g;
[0008] Preferably, the pore volume of the composite catalyst material is 0.60-0.84 cm 3 / g, average pore size of 3.5-5.0nm, specific surface area of 440-520m 2 / g.
[0009] The present invention provides a method for preparing the composite catalytic material, comprising the following steps:
[0010] 1) mixing a metallic lanthanum inorganic compound, a metallic cadmium inorganic compound and an inorganic acid solution to obtain a mixed solution;
[0011] 2) adding the natural colloidal powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, and drying and grinding to obtain a composite powder;
[0012] 3) The composite powder obtained in step 2) is mixed with aluminosilicate and calcined to obtain the composite catalytic material.
[0013] Preferably, in step 1), after the metallic lanthanum inorganic compound and the metallic cadmium inorganic compound are placed in an organic alcohol, an inorganic acid solution is added and mixed to obtain a mixed solution.
[0014] Preferably, the metallic lanthanum inorganic compound is selected from at least one of lanthanum oxide and inorganic lanthanum salt;
[0015] Preferably, the metallic lanthanum inorganic compound is selected from at least one of lanthanum oxide, lanthanum chloride and lanthanum nitrate;
[0016] The metallic cadmium inorganic compound is selected from at least one of cadmium oxide and inorganic cadmium salt;
[0017] Preferably, the metallic cadmium inorganic compound is selected from at least one of cadmium oxide, cadmium chloride and cadmium nitrate;
[0018] The organic alcohol is selected from at least one of ethanol, propanol and isopropanol;
[0019] The inorganic acid in the inorganic acid solution is selected from at least one of hydrochloric acid, boric acid and phosphoric acid;
[0020] The molar concentration of the inorganic acid in the inorganic acid solution is 1-3 mol / L;
[0021] The mixing temperature in step 1) is 30-40°C and the mixing time is 20-36h;
[0022] In step 1), the molar ratio of the metal lanthanum ions in the metal lanthanum inorganic compound, the metal cadmium ions in the metal cadmium inorganic compound, and the inorganic acid in the inorganic acid solution is 1:(1-4):(1.9-3.1);
[0023] The volume ratio of the organic alcohol to the inorganic acid solution is (100-200):(100-200).
[0024] Preferably, the natural colloidal powder in step 2) is selected from at least one of sesbania gum powder, guar gum powder and konjac gum powder;
[0025] The mass ratio of the total mass of the metallic lanthanum inorganic compound and the metallic cadmium inorganic compound to the mass of the natural colloidal powder is 1:(0.1-1).
[0026] The drying temperature in step 2) is 65-85°C and the drying time is 3-5h;
[0027] The colloidal mixture in step 2) further comprises a washing step before drying;
[0028] Optionally, the washing includes washing the colloidal mixture with an ethanol aqueous solution having an ethanol mass concentration of 30-50% to a pH of 7-7.2.
[0029] Optionally, the sesbania gum powder includes natural sesbania gum colloid and its derivatives, the guar gum powder includes natural guar gum and its derivatives, and the konjac gum powder includes natural konjac gum colloid and its derivatives.
[0030] Optionally, the particle size of the natural colloidal powder is 45-120 mesh.
[0031] Preferably, the aluminosilicate in step 3) is selected from at least one of kaolin, diatomaceous earth and montmorillonite;
[0032] The mass ratio of the aluminosilicate to the natural colloidal powder is (0.3-3.1):1.
[0033] Preferably, in step 3), the composite powder obtained in step 2), aluminosilicate and water are mixed, extruded, dried and calcined to obtain the composite catalytic material;
[0034] Preferably, the mass ratio of the aluminosilicate to water in step 3) is (0.2-4):1;
[0035] The drying temperature is 110-130°C and the drying time is 2h-4h;
[0036] The calcination temperature is 520-580° C., and the calcination time is 2 h-4 h.
[0037] The present invention provides an application of the composite catalytic material described above in removing H2O and / or sulfide from gas;
[0038] Optionally, the use conditions of the composite catalytic material for removing H2O and / or sulfide in gas are: reaction temperature of 21-25°C, reaction space velocity of 900-1200h -1 .
[0039] Optionally, the reaction pressure of the composite catalytic material when removing H2O and / or sulfide in the gas is 80-120 KPa, for example, the reaction pressure can be selected to be normal pressure.
[0040] The present invention has no specific limitation on the gas, and any gas that needs to remove H2O and / or sulfide can be used. For example, optionally, the gas is nitrogen with a water content of 500-600 ppm, and optionally, the gas is nitrogen with a H2S content of more than 200 ppm.
[0041] The technical solution of the present invention has the following advantages:
[0042] 1. The composite catalytic material provided by the present invention comprises a carrier and an active ingredient; the carrier is a mesoporous silica-alumina material; the active ingredients are lanthanum oxide and cadmium oxide. The present invention adopts lanthanum oxide and cadmium oxide as active ingredients. There are unsaturated sites on the surface of lanthanum oxide and cadmium oxide. These unsaturated sites have the ability to react chemically with other atoms or molecules, thereby causing lanthanum oxide and cadmium oxide to be active in the catalytic reaction. Mesoporous materials have the characteristics of high specific surface area, high chemical stability, convenient synthesis and low price, and can achieve good separation and adsorption. In the present invention, the composite catalytic material formed by the coordinated cooperation of lanthanum oxide, cadmium oxide and mesoporous silica-alumina materials has excellent dehydration and desulfurization effects.
[0043] 2. The preparation method of the composite catalytic material provided by the present invention comprises the following steps: 1) mixing a metal lanthanum inorganic compound, a metal cadmium inorganic compound and an inorganic acid solution to obtain a mixed solution; 2) adding natural colloidal powder to the mixed solution obtained in step 1) and stirring and mixing to form a colloidal mixed solution, and obtaining a composite powder through drying and grinding; 3) mixing the composite powder obtained in step 2) with aluminosilicate, and calcining to obtain the composite catalytic material. The present invention first carries metal lanthanum ions and metal cadmium ions on natural colloidal powder, and then mixes with aluminosilicate, extrudes strips, and calcines to obtain the composite catalytic material. The active component is combined with the natural colloidal powder by intermolecular force, and then kneaded with the aluminosilicate. After calcination, the natural colloidal powder volatilizes in the form of water vapor and carbon dioxide, thereby controlling the pore size of the silicon-aluminum mesoporous material, and at the same time, the active component is efficiently and evenly dispersed on the silicon-aluminum mesoporous material. The composite mesoporous catalytic material has a large pore volume, a large specific surface area and an orderly pore structure. The mesoporous pore structure fixed on the mesoporous wall can make the active components fully contact the active sites, and can have dehydration and desulfurization capabilities, with excellent dehydration and desulfurization effects.
[0044] 3. The preparation method of the composite catalyst material provided by the present invention, the natural colloid powder described in step 2) is selected from at least one of sesbania gum powder, guar gum powder and konjac gum powder; the present invention selects specific natural colloid powders with extremely strong water solubility, and can form high-viscosity colloids to enhance the cohesiveness of the composite catalyst when it meets water, so that the active ingredients in the composite catalyst are dispersed more evenly, and the chemical stability of the composite catalyst is further enhanced. When the specific natural colloid powder acts on the active metal, electron transfer, physical action, and chelation of metal ions and the hydroxyl groups of the natural colloid occur, thereby achieving efficient catalytic effect, and further improving the dehydration and desulfurization effect of the composite catalyst material.
[0045] 4. The preparation method of the composite catalytic material provided by the present invention has a simple preparation process and can be achieved without harsh conditions. DETAILED DESCRIPTION
[0046] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0047] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0048] The particle size of the sesbania gum powder used in the examples and comparative examples of the present invention is 100 mesh, the particle size of the guar gum powder is 100 mesh, and the particle size of the konjac gum powder is 100 mesh.
[0049] Example 1
[0050] This embodiment provides a method for preparing a composite catalytic material, comprising the following steps:
[0051] 1) 24.53 g of lanthanum chloride and 36.66 g of cadmium chloride were placed in 120 ml of ethanol in a 30° C. constant temperature water bath, and 200 ml of a 1 mol / L hydrochloric acid aqueous solution was added thereto for mechanical stirring and mixing for 20 h to obtain a mixed solution;
[0052] 2) adding 11.65 g of sesbania gum powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, washing the colloidal mixed solution with an ethanol aqueous solution having an ethanol mass concentration of 30% to a pH of 7, then filtering, drying at 65° C. for 4 h, and grinding to obtain a composite powder;
[0053] 3) The composite powder obtained in step 2) is mixed with 3.50 g of diatomaceous earth and 10.5 g of water, extruded into strips, dried at 120° C. for 2 h, and then calcined at 550° C. for 2 h to obtain the composite catalytic material.
[0054] Example 2
[0055] This embodiment provides a method for preparing a composite catalytic material, comprising the following steps:
[0056] 1) 24.53 g of lanthanum chloride and 54.99 g of cadmium chloride were placed in 150 ml of ethanol in a 35° C. constant temperature water bath, and 100 ml of a 2 mol / L hydrochloric acid aqueous solution was added thereto for mechanical stirring and mixing for 28 h to obtain a mixed solution;
[0057] 2) adding 35.5 g of sesbania gum powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, washing the colloidal mixed solution with an ethanol aqueous solution having an ethanol mass concentration of 30% to a pH of 7, then filtering, drying at 75° C. for 4 h, and grinding to obtain a composite powder;
[0058] 3) The composite powder obtained in step 2) is mixed with 35.5 g of kaolin and 35.5 g of water, extruded into strips, dried at 120° C. for 3 h, and then calcined at 550° C. for 3 h to obtain the composite catalytic material.
[0059] Example 3
[0060] This embodiment provides a method for preparing a composite catalytic material, comprising the following steps:
[0061] 1) 24.53 g of lanthanum chloride and 73.32 g of cadmium chloride were placed in 150 ml of ethanol in a constant temperature water bath at 40° C., and 100 ml of a 3 mol / L hydrochloric acid aqueous solution was added thereto and mechanically stirred and mixed for 36 hours to obtain a mixed solution;
[0062] 2) adding 67.15 g of sesbania gum powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, washing the colloidal mixed solution with an ethanol aqueous solution having an ethanol mass concentration of 30% to a pH of 7, then filtering, drying at 85° C. for 4 h, and grinding to obtain a composite powder;
[0063] 3) The composite powder obtained in step 2) is mixed with 201.46 g of montmorillonite and 60.44 g of water, extruded into strips, dried at 120° C. for 4 h, and then calcined at 550° C. for 4 h to obtain the composite catalytic material.
[0064] Example 4
[0065] This embodiment provides a method for preparing a composite catalytic material, comprising the following steps:
[0066] 1) 16.29 g of lanthanum oxide and 25.68 g of cadmium oxide were placed in 100 ml of propanol in a 30° C. constant temperature water bath, and 200 ml of a 1 mol / L phosphoric acid aqueous solution was added thereto for mechanical stirring and mixing for 20 hours to obtain a mixed solution;
[0067] 2) adding 11.65 g of guar gum powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, washing the colloidal mixed solution with an ethanol aqueous solution having an ethanol mass concentration of 30% to a pH of 7, then filtering, drying at 65° C. for 4 h, and grinding to obtain a composite powder;
[0068] In step 3), the composite powder obtained in step 2) is mixed with 3.50 g of kaolin and 15.5 g of water, extruded into strips, dried at 120° C. for 2 h, and then calcined at 550° C. for 2 h to obtain the composite catalytic material.
[0069] Example 5
[0070] This embodiment provides a method for preparing a composite catalytic material, comprising the following steps:
[0071] 1) 32.49 g of lanthanum nitrate and 94.4 g of cadmium nitrate were placed in 200 ml of isopropanol in a constant temperature water bath at 40° C., and 100 ml of a 3 mol / L boric acid aqueous solution was added thereto for mechanical stirring and mixing for 36 hours to obtain a mixed solution;
[0072] 2) adding 67.15 g of konjac gum powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, washing the colloidal mixed solution with an ethanol solution having an ethanol mass concentration of 30% to a pH of 7, then filtering, drying at 85° C. for 4 h, and grinding to obtain a composite powder;
[0073] 3) The composite powder obtained in step 2) is mixed with 201.46 g of montmorillonite and 60.44 g of water, extruded into strips, dried at 120° C. for 4 h, and then calcined at 550° C. for 4 h to obtain the composite catalytic material.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a composite catalytic material, which differs from Example 2 in that an equal molar amount of lanthanum chloride is used to replace cadmium chloride in step 1).
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing a composite catalytic material, which differs from Example 2 in that an equal molar amount of cadmium chloride is used to replace lanthanum chloride in step 1).
[0078] Test Example 1
[0079] The composite catalytic material samples prepared in the above Examples 1-5 and Comparative Examples 1-2 were respectively tested for specific surface area, pore volume and average pore size of the calcined composite catalytic materials using a physical adsorption instrument (model ASAP2460, Micromeritics Instruments, USA), and the test results are shown in Table 1. Specific surface area is an important indicator for measuring catalyst activity, adsorption performance and reaction capacity; average pore size analysis is of great significance for understanding the adsorption performance of the catalyst.
[0080] Table 1
[0081]
[0082] Test Example 2
[0083] The composite catalytic materials prepared in the above Examples 1-5 and Comparative Examples 1-2 were subjected to a dehydration test, comprising the following steps: the reaction tube was a hard glass tube with an inner diameter of 20 mm; the composite catalyst loading was 10 mL (particle size 20-40 mesh); the raw gas was nitrogen with a water content of 600 ppm; the dehydration reaction conditions were: normal pressure, 25 ° C, and a reaction space velocity of 1000 h -1 ; A water vapor detection tube was used to detect the water content in the gas after adsorption. The water removal rate = (water content in the raw gas - water content in the gas after adsorption) / water content in the raw gas * 100%. The results of the water removal rate of the composite catalytic material are shown in Table 2.
[0084] Table 2
[0085] Water removal rate (%) Example 1 94.3 Example 2 96.3 Example 3 95.7 Example 4 93.0 Example 5 94.8 Comparative Example 1 91.2 Comparative Example 2 91.0
[0086] Test Example 3
[0087] The desulfurization parameters of the composite catalytic materials prepared in the above Examples 1-5 and Comparative Examples 1-2 include the following steps: the reaction tube is a hard glass tube with an inner diameter of 8 mm; the composite catalyst loading is 1 mL (particle size 20-40 mesh); the raw gas is nitrogen containing 200 ppm H2S; the adsorption reaction conditions are: 25°C, normal pressure; the reaction space velocity is 1000 h -1 ; Gas chromatograph was used to detect the H2S content in the gas after adsorption. H2S removal rate = (H2S content in raw gas - H2S content in gas after adsorption) / H2S content in raw gas * 100%. The results of H2S removal rate of composite catalytic materials are shown in Table 3.
[0088] Table 3
[0089]
[0090]
[0091] It can be seen from the above table that the catalyst prepared in Example 2 has a better dehydration and desulfurization effect because the adsorption mainly occurs at the active sites on the surfaces of lanthanum oxide and cadmium oxide metals, and because the natural polymer organic material can effectively disperse the active metal components, the contact area between the metal active sites and the reactants is increased, thereby improving its dehydration and desulfurization effect; compared with Example 2, the catalysts in Examples 1 and 4 have poor desulfurization and dehydration effects because the amount of silicon-aluminum material added is small, and the active components cannot be effectively dispersed. During the preparation process, the catalyst forms large particles, which affects the uniformity of the catalyst particles and reduces the active sites of the catalytic material; the catalysts in Examples 3 and 5 have a lower specific surface area, and the contact area between the metal active sites and the reactants in the adsorbed gas is small, which also leads to lower desulfurization and dehydration capabilities; Comparative Examples 1 and 2 have low desulfurization and dehydration capabilities because the single metal active sites are low.
[0092] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A composite catalytic material, characterized in that: The composite catalytic material includes a carrier and an active component; The carrier is a mesoporous silicon-aluminum material; The active ingredients are lanthanum oxide and cadmium oxide.
2. The composite catalytic material according to claim 1, characterized in that: The pore volume of the composite catalytic material is 0.57-0.84 cm 3 / g, average pore size of 3.2-5.2nm, specific surface area of 420-520m 2 / g; Preferably, the pore volume of the composite catalyst material is 0.60-0.84 cm 3 / g, average pore size of 3.5-5.0nm, specific surface area of 440-520m 2 / g.
3. A method for preparing the composite catalytic material according to claim 1 or 2, characterized in that: The following steps are involved: 1) mixing a metallic lanthanum inorganic compound, a metallic cadmium inorganic compound and an inorganic acid solution to obtain a mixed solution; 2) adding the natural colloidal powder to the mixed solution obtained in step 1) and stirring to form a colloidal mixed solution, and drying and grinding to obtain a composite powder; 3) The composite powder obtained in step 2) is mixed with aluminosilicate and calcined to obtain the composite catalytic material.
4. The method for preparing the composite catalytic material according to claim 3, characterized in that: In step 1), the metal lanthanum inorganic compound and the metal cadmium inorganic compound are placed in an organic alcohol, and then an inorganic acid solution is added to mix them to obtain a mixed solution.
5. The method for preparing the composite catalytic material according to claim 4, characterized in that: The metallic lanthanum inorganic compound is selected from at least one of lanthanum oxide and inorganic lanthanum salt; Preferably, the metallic lanthanum inorganic compound is selected from at least one of lanthanum oxide, lanthanum chloride and lanthanum nitrate; The metallic cadmium inorganic compound is selected from at least one of cadmium oxide and inorganic cadmium salt; Preferably, the metallic cadmium inorganic compound is selected from at least one of cadmium oxide, cadmium chloride and cadmium nitrate; The organic alcohol is selected from at least one of ethanol, propanol and isopropanol; The inorganic acid in the inorganic acid solution is selected from at least one of hydrochloric acid, boric acid and phosphoric acid; The molar concentration of the inorganic acid in the inorganic acid solution is 1-3 mol / L; The mixing temperature in step 1) is 30-40°C and the mixing time is 20-36h; In step 1), the molar ratio of the metal lanthanum ions in the metal lanthanum inorganic compound, the metal cadmium ions in the metal cadmium inorganic compound, and the inorganic acid in the inorganic acid solution is 1:(1-4):(1.9-3.1); The volume ratio of the organic alcohol to the inorganic acid solution is (100-200):(100-200).
6. The method for preparing the composite catalytic material according to any one of claims 3 to 5, characterized in that: The natural colloidal powder in step 2) is selected from at least one of sesbania gum powder, guar gum powder and konjac gum powder; The mass ratio of the total mass of the metal lanthanum inorganic compound and the metal cadmium inorganic compound to the mass ratio of the natural colloidal powder is 1:(0.1-1); The drying temperature in step 2) is 65-85°C and the drying time is 3-5h; The colloidal mixture in step 2) further comprises a washing step before drying; Optionally, the washing includes washing the colloidal mixture with an ethanol aqueous solution having an ethanol mass concentration of 30-50% to a pH of 7-7.
2.
7. The method for preparing the composite catalytic material according to any one of claims 3 to 6, characterized in that: The aluminosilicate in step 3) is selected from at least one of kaolin, diatomaceous earth and montmorillonite; The mass ratio of the aluminosilicate to the natural colloidal powder is (0.3-3.1):
1.
8. The method for preparing the composite catalytic material according to any one of claims 3 to 7, characterized in that: In step 3), the composite powder obtained in step 2), aluminosilicate and water are mixed, extruded into strips, dried and calcined to obtain the composite catalytic material.
9. The method for preparing the composite catalytic material according to claim 8, characterized in that: The mass ratio of the aluminosilicate to water in step 3) is (0.2-4):1; The drying temperature is 110-130°C and the drying time is 2h-4h; The calcination temperature is 520-580° C., and the calcination time is 2 h-4 h.
10. Use of the composite catalytic material according to claim 9 in removing H2O and / or sulfide from gas; Optionally, the use conditions of the composite catalytic material for removing H2O and / or sulfide in gas are: reaction temperature of 21-25°C, reaction space velocity of 900-1200h -1 .